Documentation of Pregnancy Risk Assessment and Pregnancy Among Women Presenting for Gynecologic Oncology Consultation. Issue 1 (January 2016) - Crafton, Sarah; Nekkanti, Silpa; Lynch, Courtney; Cohn, David E.; Fowler, Jeffrey M.; Copeland, Larry J.; O'Malley, David M.; Salani, Ritu; Backes, Floor J.; Eisenhauer, Eric L.
Abstract : Objective: The aim of the study was to describe pregnancy risk assessment, reproductive goals, and incidence of pregnancy among the reproductive age population seen by gynecologic oncologists at a tertiary care center. Methods: A retrospective chart review was conducted among 18- to 45-year-old women evaluated by a gynecologic oncologist from January 2000 to December 2011. Data abstracted included the following: diagnosis, cancer treatment, parity, pregnancy risk factors (eg, menstrual patterns, sexual activity, and use of contraception), reproductive goals, type of referral, and pregnancy. Descriptive statistics were used to describe the characteristics of the population. Results: Five hundred seventeen women were eligible and included in the review. Median age was 31 years with most common diagnoses being cervical cancer, endometrial cancer, and premalignant disease. Most patients are multiparous. Seventy percent were treated surgically, with 58% experiencing surgical sterility. Completeness of reproductive data documented at initial visit included the following: 47% with a contraception plan, 54% sexual activity/practices, and 37% with personal reproductive goals reviewed. Fifteen patients were pregnant at the initial visit, and 21 patients pregnant during follow-up, representing 43 pregnancies (9 patients had more than 1 pregnancy). For those maintaining fertility after the initial visit, there was a median (range) of 2 (0–25) visits with 32% documenting a contraception plan at follow-up visits. Conclusions: A patient's reproductive goals and risk factors for pregnancy are inconsistently addressed during initial consultation with the gynecologic oncologist. This lack of consistency potentially increases patients' risk for unplanned pregnancy during evaluation and treatment of a gynecologic cancer diagnosis and potentially results in a missed opportunity for fertility preservation. Planned and unplanned pregnancy occurs in this population at a rate similar to that of US women of reproductive age, underscoring the need for reproductive counseling in this population.